1948
DOI: 10.1021/ie50465a025
|View full text |Cite
|
Sign up to set email alerts
|

Butyl Alcohol from Xylose Saccharification Liquors from Corncobs

Abstract: No. 9 reasonable agreement with that measured in cotton after chromium shadowing. SUMMARYThe results of this investigation offer additional evidence in support of a fibrillak structure for natural cellulose. The coarse fibrils commonly observed by optical and electron microscopy are shown b metallic shadow casting to consist of still finer unit fibrils. h , h o u g h the diameters of these fine fibrils vary somewhat in s, single sample, greater differences in this respect .prevail among fibers of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1951
1951
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Prospects of utilization of hydolyzates for ABE fermentation have been investigated for more than half a century. Earliest studies in this area include those of Waksman and Kirsh [124], Underkofler et al [125], Sjolander et al [126], Leonard et al [127], Langlykke et al [128], and Nakhmanovich and Shcheblykina [20].…”
Section: Substrates For Acetone-butanol-ethanol Fermentationmentioning
confidence: 99%
“…Prospects of utilization of hydolyzates for ABE fermentation have been investigated for more than half a century. Earliest studies in this area include those of Waksman and Kirsh [124], Underkofler et al [125], Sjolander et al [126], Leonard et al [127], Langlykke et al [128], and Nakhmanovich and Shcheblykina [20].…”
Section: Substrates For Acetone-butanol-ethanol Fermentationmentioning
confidence: 99%
“…Hydrolysates. Initial studies (131,137,190,233,252,266) suggested that acid hydrolysis of cellulosic material from a variety of sources offered possibilities as a substrate for AB fermentation, and more recently Saddler and his co-workers have investigated the production and utilization of wood cellulose and hemicellulose hydrolysates (226,290,291,293). Steam-exploded wood chips were extracted with water, and over 75% of the hemicellulose was shown to be present in the water-soluble fraction, leaving a celluloserich, water-insoluble substrate which could be readily hydrolyzed to glucose.…”
Section: Substrates Derived From Lignocellulosementioning
confidence: 99%
“…The solventproducing strains of Clostridium sp. are capable of fermenting a wide variety of carbohydrates, including hexoses (6) and pentoses (9,14,19). The potential of these strains for the industrial production of acetone, n-butanol, and ethanol would be greatly enhanced if they were able to hydrolyze cellulose.…”
mentioning
confidence: 99%